Реконструкція та верифікація просторової структури молекул тубулінів представників Diplomonadida, Kinetoplastida, Amoebida, Saccharomycetes та Microsporea - Співак, С.І.; Ожерєдов, С.П.; Самофалова, Д.О.; Раєвський, О.В.; Карпов, П.А. (Фактори експериментальної еволюції організмів, 2015)
Aims. The purpose of this study was a reconstruction and verification of spatial structures of tubulin molecules from representatives of Diplomonadida, Kinetoplastida, Amoebida, Saccharomycetes and Microsporea to determine differences in their spatial structures and clarify the mechanism of their interaction with antimitotic agents. Methods. The study was carried out with in silico approaches using UniProtКВ database, RCSB Protein Data Bank and on-line services: SWISSMODEL, I-TASSER and MolProbity. Results. 17 tubulin molecules with fully decoded primary structures were selected among representatives of such classes: Diplomonadida, Kinetoplastida, Amoebida, Saccharomycetes and Microsporea. For all these proteins accurate three dimentional structures were constructed with subsequent optimization and verification of protein geometry. Conclusions. Selected models of tubulin molecules were added to a CSModDB database within VO CSLabGrid for their future application in comparative analysis and a search of compounds with anti mitotic activity by means of high-throughput screening. Keywords: tubulin, antimitotic drugs, in silico.